PENENTUAN PRIORITAS PEMBANGUNAN DESA RENGEL BERBASIS SISTEM PENDUKUNG KEPUTUSAN DENGAN METODE FAHP-WP - Izra Noor Zahara Aliya; Rizka Hadiwiyanti; Reisa Permatasari (Journal of Information Technology and Its Utilization, 2024)
Villages play a strategic role in national development, particularly in improving the quality of life and community welfare. Rengel Village, located in Tuban Regency, East Java, holds significant potential for development. However, decision-making in development through the “Musrenbangdes” (village development planning forum) is often hindered by conflicts of interest between neighborhood units (RT and RW) and the lack of an objective system to assess priorities. Therefore, a Decision Support System (DSS) utilizing the Fuzzy Analytic Hierarchy Process (F-AHP) and Weighted Product (WP) methods is needed to prioritize development. F-AHP determines criterion weights based on relative importance and addresses uncertainty in assessments, while WP ranks alternatives based on these weights. This study involves data collection, calculation of criterion weights, alternative development ranking, system development, and deriving conclusions. The results show that the CR value of 0.033 indicates a good level of consistency in comparisons, yielding the following criterion weights: RPJM (0.331), Urgency Level (0.278), Impact and Benefits (0.237), Regulatory Compliance (0.14), and Budget (0.014). Meanwhile, the alternative development ranking results indicate the following priority order: AP41 (1), AP06 (2), AP33 (3), AP49 (4), AP12 (5), AP40 (6), AP13 (7), AP11 (8), AP43 (9), and AP28 (10).